STUDY OF THE EFFECT OF EXPERIMENTAL CHRONIC CARBON MONOXIDE INTOXICATION ON THE MORPHOLOGICAL AND MORPHOMETRIC FEATURES OF THE FRONTAL CORTEX OF THE CEREBRAL HEMISPHERES IN OUTBRED ALBINO RATS AGED 3, 9, AND 18 MONTHS - Sh.Ya. Bakhronov; L.J. Sultonova (Journal of modern medicine, 2026)
The aim of the study was to investigate the effects of experimental chronic carbon monoxide intoxication on the morphological and morphometric characteristics of the frontal cortex of the cerebral hemispheres in 3, 9, and 18 month-old outbred rats. The experiment included 45 male rats divided into control and experimental groups. Chronic carbon monoxide intoxication was modeled in a hermetically sealed chamber for one month at a CO concentration of 0.01-0.05 mg/L in the air. Morphological changes were assessed in histological sections stained with hematoxylin and eosin, while morphometric parameters were evaluated based on the thickness of the molecular, external granular, and external pyramidal layers of the frontal cortex. The findings demonstrated an age-related increase in morphological remodeling of the frontal cortex under chronic carbon monoxide intoxication.